2019
DOI: 10.1007/s10439-019-02206-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-214 is Stretch-Sensitive in Aortic Valve and Inhibits Aortic Valve Calcification

Abstract: miR-214 has been recently found to be significantly downregulated in calcified human aortic valves (AVs). ER stress, especially the ATF4-mediated pathway, has also been shown to be significantly upregulated in calcific AV disease. Since elevated cyclic stretch is one of the major mechanical stimuli for AV calcification and ATF4 is a validated target of miR-214, we investigated the effect of cyclic stretch on miR-214 expression as well as those of ATF4 and two downstream genes (CHOP and BCL2L1). Porcine aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…A study using human aortic VECs demonstrated that that shear stress may regulate Notch1 signaling (White et al, 2015). Additional in vitro studies have suggested that shear-sensitive microRNAs (miRNAs) may also be involved in CAVD (Holliday et al, 2011;Fernandez Esmerats et al, 2019;Salim et al, 2019). Another study identified two families with early onset progressive heart valve disease caused by a homozygous mutation in ADAMTS19 (Wünnemann et al, 2020).…”
Section: Developmental Mechanisms Implicated In Valve Diseasementioning
confidence: 99%
“…A study using human aortic VECs demonstrated that that shear stress may regulate Notch1 signaling (White et al, 2015). Additional in vitro studies have suggested that shear-sensitive microRNAs (miRNAs) may also be involved in CAVD (Holliday et al, 2011;Fernandez Esmerats et al, 2019;Salim et al, 2019). Another study identified two families with early onset progressive heart valve disease caused by a homozygous mutation in ADAMTS19 (Wünnemann et al, 2020).…”
Section: Developmental Mechanisms Implicated In Valve Diseasementioning
confidence: 99%
“…The different patterns of blood flow experienced either side of the aortic valve have also been implicated in expression of HIF-1 α . It has been shown that disturbed patterns of flow, characteristic of the aortic side of the valve, are associated with expression of HIF-1 α , miR-483, ubiquitin E2 ligase C and von Hippel-Lindau protein, which have all been shown to be flow-sensitive molecules 52 . Under conditions of disturbed flow, von Hippel-Lindau Protein is degraded by ubiquitin E2 Ligase C, causing HIF-1 α levels to rise.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical stress is an important environmental stimulus for regulating cell physiology and morphology [10][11][12][13][14]. The effects of cyclic stretching, in addition to tensile stress and fluid shear stress, have been investigated in various cell types [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%